2015
DOI: 10.1155/2015/612341
|View full text |Cite
|
Sign up to set email alerts
|

Combustion of Biogas Released from Palm Oil Mill Effluent and the Effects of Hydrogen Enrichment on the Characteristics of the Biogas Flame

Abstract: Biogas released from palm oil mill effluent (POME) could be a source of air pollution, which has illustrated negative effects on the global warming. To protect the environment from toxic emissions and use the energy of POME biogas, POME is conducted to the closed digestion systems and released biogas is captured. Since POME biogas upgrading is a complicated process, it is not economical and thus new combustion techniques should be examined. In this paper, POME biogas (40% CO2and 60% CH4) has been utilized as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
(52 reference statements)
0
7
0
1
Order By: Relevance
“…However, the principal matter that constrain the production is the complexity of the overall production, which elevates the cost of the biogas. Hosseini et al [128] introduced H 2 with POME biogas, which visibly stretches the formation of flame and improved the low calorific biogas nature by increasing the percentage of H 2 from 5 to 10%. The only drawback of this method is that it produces NO X , enhanced via the temperature [128].…”
Section: The Production Of Gaseous Biofuelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the principal matter that constrain the production is the complexity of the overall production, which elevates the cost of the biogas. Hosseini et al [128] introduced H 2 with POME biogas, which visibly stretches the formation of flame and improved the low calorific biogas nature by increasing the percentage of H 2 from 5 to 10%. The only drawback of this method is that it produces NO X , enhanced via the temperature [128].…”
Section: The Production Of Gaseous Biofuelmentioning
confidence: 99%
“…Hosseini et al [128] introduced H 2 with POME biogas, which visibly stretches the formation of flame and improved the low calorific biogas nature by increasing the percentage of H 2 from 5 to 10%. The only drawback of this method is that it produces NO X , enhanced via the temperature [128]. Bukhari et al identified that cofiring of biogas in palm oil mill boilers could potentially reduce the formation of PM by up to 50% and provide fuel saving by up to 80-90% [129].…”
Section: The Production Of Gaseous Biofuelmentioning
confidence: 99%
“…The temperature and composition of combustion product gases are also important parameters in equipment design of biogas system. Previous researches had studied the combustion characteristic of biogas, many researchers studied the combustion performance of biogas in internal combustion SI and CI engine [8,[12][13][14][15][16][17][18][19][20], the characteristics in microgas turbine [21][22][23] and also specifically on the characteristics in biogas burner [5,[24][25][26][27][28][29][30]. Largely, the previous researches of combustion in biogas burner were done in a certain methane content of biogas, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Largely, the previous researches of combustion in biogas burner were done in a certain methane content of biogas, i.e. 40% [29], 51% [31], 60% [5,[27][28][29], 61% [29][30], and also 100% [29]. The burners used were burner for gas turbine configuration [30], MILD or flameless burner [28], and lab scale furnace [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation